Grin of Empire: Modelling of Russian Bear in Foreign Multimodal Media Texts - Maria V. Plotnikova; Ivan V. Suslov (Галактика медиа: журнал медиа исследований)
The article is devoted to the image of Russia modelling through the zoomorphic conceptual metaphor of Russian bear in foreign multimodal texts. The metaphorical image is analyzed retrospectively to identify both common and specific features in different languages and cultures. We also detect a correlation between the positive and negative representation of this image depending on the socio-political context. The authors focus on various ways of interpreting and transforming the image of the Russian bear in multimodal media texts of different genres. The study revealed the prevalence of a negative interpretation of the image of the Russian bear over a positive and neutral one. The most frequent is the use of the metaphor of an aggressive, bloodthirsty Russian bear in relation to the reference situation of military conflicts involving Russia. In political cartoons, such a metaphorical image is often modelled by associative signs of aggression: claws and fangs, and suggests the presence of a “victim” in the iconic part of the multimodal text. Cinematography enhances the mythologization of the metaphorical image in question. At the same time, the connection of the bear with Russia is expressed indirectly: the image of the bear can accompany Russian characters, localize the territory of Russia, due to the presence of a bear in the frame, depict Russians visually similar to bears. The replication of stereotypical metaphorical images creates a stable negative scenario in the recipients’ consciousness, an invariant in relation to a certain conceptual category; therefore, it has an evident manipulative potential.